The Campus as Crucible: A Critical Race Analysis of Campus Climate in the Experiences of American Muslim Undergraduates. Issue 5 (May 2019) - Ali, Arshad Imtiaz
Background/Context: Muslim communities in the United States have increasingly been the target of the state security apparatus, virulent public discourse, and increasing cultural xenophobia. Since 2001, individuals perceived to be from Muslim backgrounds have experienced dramatically increasing numbers of racially motivated attacks. What is often called "Islamophobia, " or anti-Muslim discrimination or racism, has continued to rise in the past decade. Muslim communities face an acute political and cultural attack in which their actions and words are increasingly scrutinized and questioned. College campuses have been particular sites of contestation. This article explores how Muslim undergraduates understand their campus experiences. Purpose/Objective/Focus of Study: I examine how Muslim students expressed feelings of isolation and alienation on their campus community in a context of state surveillance programs targeting Muslim students and communities. In particular, I explore student narratives of being conscious of peer suspicion. Further, I investigate how self-consciousness of their outsider status created an environment where Muslim students feel they must continually attempt to make their peers comfortable with their presence while also challenging dominant stereotypes of Muslims. This study gives voice to Muslim undergraduate students as they negotiate prejudices, scrutiny, and discrimination on college campuses. Setting: Data was collected in southern California because there is a critical mass of community, concentration of students, and number of political advocacy and service providers for the diverse Muslim communities in the region. Focusing on this age group allows for an examination of this specific generation's understandings of race, identity, and citizenship, because they came of age amidst a rise in discrimination and racism against those associated with Islam and Muslims. Data Collection and Analysis: Data was collected through semi-structured life history interviews and ethnographic observations of Muslim undergraduates in Southern California. The interviews spanned between three and five hours each and were conducted over multiple meetings with each participant. Drawing from a critical feminist framework, interviews were conducted not simply to garner data, but rather to allow students the opportunity explore their own experiences, analyze their histories, and engage in social analysis. The research utilized a multi-level coding scheme in order to understand individual meaning-making processes. Findings/Results: This study reveals that Muslim students often feel politically and culturally targeted and isolated on their campuses and do not feel that their peers and teachers engage with them as full members of the campus community. Conclusions: This study contributes to the growing body of literature that demonstrates the multiracial demographic of students who choose the term Muslim as a primary form of identity. This study reveals that Muslim students often felt politically and culturally targeted and isolated on their campuses and did not feel that their peers and teachers engaged with them as full members of the campus community. Colleges and universities must take proactive steps to engage Muslim students in dialogue about their concerns, fears, and questions about issues of freedoms and protections on campus.